Justice Frank Iacobucci and the Search for Truth and Reconciliation in Canada - O’Handley, Andrew (Italian Canadiana)

(untitled) (Iter Press, 2022)
In this radio interview, Justice Frank Iacobucci shares his insights into the legal, political, and ethical forces behind The Indian Residential Schools Settlement Agreement (2007) and The Truth and Reconciliation Commission (2007–2015). These initiatives were designed to address the many serious issues and injustices that have long impacted Indigenous peoples and continue to radically reshape First Nation communities in Canada.